A3.28 Screening of sphingolipids in SLE – before and after treatment. (31st January 2014) - Idborg, Helena; Checa, Antonio; Sar, Daniel; Jakobsson, Per-Johan; Wheelock, Craig; Gunnarsson, Iva
Abstract : Background and Objectives: Systemic lupus erythematosus (SLE) is an autoimmune disease with a heterogeneous presentation of symptoms from joints, skin, kidneys, central nervous system, lungs, and the cardiovascular system. There is no cure for SLE and the development of drugs are hampered due to the heterogeneity of the disease. Therefore, it is important to understand and differentiate underlying biological pathways to predict prognosis and guide the choice of drugs for the individual patient. New prognostic and therapeutic biomarkers are thus imperative in SLE. Sphingolipids are bioactive signalling molecules involved in the regulation of cell growth, differentiation and apoptosis. Sphingosine-1-phosphate (S1P) has been found in increased serum concentrations in juvenile-onset SLE and ceramides and S1P might be involvedin mediating advanced vascular disease in SLE mice. In addition S1P agonist (Fingolimod) is investigated for treatment of SLE. Therefore, sphingolipids are important compounds to study in respect to SLE pathogenesis. Rituximab is a B-cell-targeting therapy and despite failure in two recent controlled trials, there has been a world-wide off-label use of Rituximab in the treatment of severe SLE. The mechanism of Rituximab is not fully understood and one reason for failed clinical trials is the difficulties in measuring endpoints, i.e., lack of biomarkers. Our objective is to study sphingolipids in patients treated with Rituximab in order to investigate the mechanism of Rituximab and suggest potential biomarkers to follow treatment. Materials and Methods: Ten SLE patients were screened for 34 different sphingolipids before and after treatment with Rituximab (n = 20). EDTA-plasma samples were extracted by liquid-liquid extraction and analysed by LC-MS/MS. Results: Sphingolipids were generally found to be down-regulated in SLE patients after treatment with Rituximab. Significant differences comparing before and after treatment were found for dihydroceramide C16:0 (p = 0.04) and glycosylceramide C16:0 (p = 0.006) on group level and for additional seven sphingolipids significance was reached comparing paired samples. Conclusions: Our results show that the sphingolipids are affected in SLE patients when treated with Rituximab and might be involved in SLE pathogenesis and therefore important drug targets to investigate further. Sphingolipids also show potential as therapeutic biomarkers of response to treatment.